ANALISIS SEKTOR POTENSIAL DI KABUPATEN INDRAMAYU - MUTHOHAROH OKTAVIANI; RIFKI KHOIRUDIN (LP2MTBM MAKARIOZ, 2021)
This study aims to determine the potential of economic sector in Indramayu District. The research method used is LocationQuotient (LQ), Shift-share Analysis, and Typology Klassen Analysis. The results showed that the basic sector in IndramayuRegency is Agricultural Sector, Mining and Quarrying Sector, and Manufacturing Processing Sector. Furthermore, the sectorthat has dominance of competitive dan specialization advantage is Agricultural Sector. Based on Klassen Typology Analysis,advanced sector in Indramayu Regency is agriculture sector.